Features of social adaptation of persons with non-chemical forms of addiction - Hanna Kotsuba (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article addressed to studying peculiarities of social adaptation of the persons with non-chemical forms of addiction. The article contains description of different forms of addictions and its psychological nature. Peculiarities of social adaptation were examined by the example of Internet addicted personalities. The article shows that Internet addicted respondents have lowered level of social intellect and at the same time they have more advanced skill to recognize the meaning of verbal messages. Computer users who have Internet addiction have such problems in communication in interpersonal sphere as excessive feeling of loneliness and interpersonal addiction.